Measuring a motivational interviewing practice orientation in criminal justice practitioners: initial validation of the response style screening questionnaire - Tafrate, Raymond Chip; Mitchell, Damon; Cox, Stephen M.; Hogan, Tom (Frontiers in Psychology, 2023)
Introduction: The use of collaborative communication techniques by criminal justice practitioners has been identified as a component of core correctional practices (CCPs). Criminal justice agencies and programs are investing in motivational interviewing (MI) training for their staff with varying intensity, follow-up coaching, and expectations for integration into practice. The present article describes the development and initial validation of the Response Style Screening Questionnaire (RSSQ), a practitioner completed tool assessing an MI-consistent practice orientation. Over three studies, we examined the factor structure, reliability, and correlations between the scale and self-reported and behavioral validity indicators. Method: Study 1 examined the factor structure of the RSSQ with a sample of 825 criminal justice practitioners. In Study 2, data from 350 probation officers completing the RSSQ alongside measures of work-orientation and attitudes was used to conduct a confirmatory factor analysis and an initial assessment of its construct validity. In Study 3, correlations between the RSSQ and audio recorded office visits of 33 probation officers coded for MI and relationship building skills examined the scale’s criterion validity. Results: In Study 1, an exploratory factor analysis with an oblique rotation yielded 18 items on four factors. In Study 2, four and five factor models were tested, with the 4-factor model of Study 1 yielding the best fit. Two of the 4 factor-derived subscales reflect styles inconsistent with MI: (1) Confrontational style, and (2) Sustain Talk style; while the remaining two reflect styles consistent with MI: (3) Eliciting style, and (4) Change Talk style. Confrontational style scores were correlated with a work-orientation reflecting probation as a law enforcement endeavor, while Eliciting and Change talk scores were correlated with a behavior change and resource broker work-orientations. In Study 3, Confrontational and Sustain Talk style scores were negatively correlated with a variety of MI skills and CCPs displayed on audio recordings, while Change Talk style scores were positively correlated with use of such skills. Discussion: Overall, the findings suggest the RSSQ is a potentially useful new practitioner self-report tool for assessing an MI practice orientation.